Factors supporting and constraining the implementation of robot-assisted surgery: a realist interview study. Issue 6 (14th June 2019) - Randell, Rebecca; Honey, Stephanie; Alvarado, Natasha; Greenhalgh, Joanne; Hindmarsh, Jon; Pearman, Alan; Jayne, David; Gardner, Peter; Gill, Arron; Kotze, Alwyn; Dowding, Dawn
Abstract : Objective: To capture stakeholders' theories concerning how and in what contexts robot-assisted surgery becomes integrated into routine practice. Design: A literature review provided tentative theories that were revised through a realist interview study. Literature-based theories were presented to the interviewees, who were asked to describe to what extent and in what ways those theories reflected their experience. Analysis focused on identifying mechanisms through which robot-assisted surgery becomes integrated into practice and contexts in which those mechanisms are triggered. Setting: Nine hospitals in England where robot-assisted surgery is used for colorectal operations. Participants: Forty-four theatre staff with experience of robot-assisted colorectal surgery, including surgeons, surgical trainees, theatre nurses, operating department practitioners and anaesthetists. Results: Interviewees emphasised the importance of support from hospital management, team leaders and surgical colleagues. Training together as a team was seen as beneficial, increasing trust in each other's knowledge and supporting team bonding, in turn leading to improved teamwork. When first introducing robot-assisted surgery, it is beneficial to have a handpicked dedicated robotic team who are able to quickly gain experience and confidence. A suitably sized operating theatre can reduce operation duration and the risk of de-sterilisation. Motivation among team members to persist with robot-assisted surgery can be achieved without involvement in the initial decision to purchase a robot, but training that enables team members to feel confident as they take on the new tasks is essential. Conclusions: We captured accounts of how robot-assisted surgery has been introduced into a range of hospitals. Using a realist approach, we were also able to capture perceptions of the factors that support and constrain the integration of robot-assisted surgery into routine practice. We have translated these into recommendations that can inform future implementations of robot-assisted surgery.